Vaginal bleeding in granuloma inguinale. Case reports. - Murugan, S (1982)
Since bleeding from the female genitourinary tract is not a common symptom in granuloma inguinale two patients presenting with profuse and intermittent vaginal bleeding were initially admitted as gynaecological or obstetric emergencies. In both cases, the cause was ultimately found to be granuloma inguinale.